22
$\begingroup$

Evaluate the integral $$\int\frac{5x^3+3x-1}{(x^3+3x+1)^3}\,dx$$

My Attempt:

Let $f(x) = \frac{ax+b}{(x^3+3x+1)^2}.$ Now differentiate both side with respect to $x$, and we get

$$ \begin{align} f'(x) &= \frac{(x^3+3x+1)^2\cdot a-2\cdot (x^3+3x+1)\cdot (3x^2+3)\cdot (ax+b)}{(x^3+3x+1)^4}\\ &= \frac{5x^3+3x-1}{(x^3+3x+1)^3}\cdot\frac{(x^3+3x+1)\cdot a-6\cdot (x^2+1)\cdot (ax+b)}{(x^3+3x+1)^3}\\ &= \frac{5x^3+3x-1}{(x^3+3x+1)^3} \frac{-5ax^3+6bx^2-3ax+(a-6b)}{(x^3+3x+1)^3}\\ &= \frac{5x^3+3x-1}{(x^3+3x+1)^3} \end{align} $$

for $a = -1$ and $b = 0$. Thus, by the Fundamental Theorem of Calculus,

$$ \begin{align} \int\frac{5x^3+3x-1}{(x^3+3x+1)^3}\,dx &= \int f'(x)\,dx\\ &= f(x)\\ &= -\frac{x}{(x^3+3x+1)^2}+\mathcal{C} \end{align} $$

How we can solve the above integral directly (maybe by using the substitution method)?

$\endgroup$
  • $\begingroup$ the solution looks very ugly $\endgroup$ – Dr. Sonnhard Graubner Jan 12 '15 at 17:38
  • 2
    $\begingroup$ You reacted very well ! I am afraid that substitution would be very difficult. $\endgroup$ – Claude Leibovici Jan 12 '15 at 17:44
  • 2
    $\begingroup$ @juantheron, Why don't you start with $$\frac{ax^2+bx+c}{(x^3+3x+1)^2}$$? $\endgroup$ – lab bhattacharjee Jan 12 '15 at 17:47
  • 1
    $\begingroup$ nice idea. how did you come to it? numerator has three degrees(may be four) how were able to handle with only two constants $a$ and $b?$ $\endgroup$ – abel Jan 12 '15 at 17:58
16
$\begingroup$

Ostrogradsky-Hermite method.

To integrate a rational function $P(x)/Q(x)$ without decomposing it into partial fractions and without finding the roots of the denominator, we can use the Ostrogradski-Hermite method, which generalizes your ansatz

$$ \int\frac{5x^3+3x-1}{(x^3+3x+1)^3}dx= \frac{ax+b}{(x^3+3x+1)^2}+C.$$

You can find a description of this method in section 2.1 of Gradshteyn and Ryzhik's Table of Integrals, Series, and Products, where the identity $(2)$ below is given. The formula $(1)$ appears also on the Ostrogradsky's Wikipedia page.

Assume that $\deg P(x)<\deg $ $Q(x)$. There exist polynomials $P_{1}(x)$, $P_{2}(x)$, $Q_{1}(x)$ and $Q_{2}(x)$, with $Q_{1}(x)=\gcd \left\{ Q(x), Q^{\prime }(x)\right\}$ and $Q_{2}(x)=Q(x)/Q_{1}(x)$, $\deg P_{1}(x)<\deg Q_{1}(x)$, $\deg P_{2}(x)<\deg Q_{2}(x)$, such that

\begin{equation} \int \frac{P(x)}{Q(x)}dx=\frac{P_{1}(x)}{Q_{1}(x)}+\int \frac{P_{2}(x)}{ Q_{2}(x)}dx.\tag{1} \end{equation}

Then

\begin{eqnarray*} P(x) &=&\frac{P_{1}^{\prime }(x)Q_{1}(x)-P_{1}(x)Q_{1}^{\prime }(x)}{\left\{ Q_{1}(x)\right\} ^{2}}Q(x)+\frac{P_{2}(x)}{Q_{2}(x)}Q(x) \\ &=&P_{1}^{\prime }(x)\frac{Q(x)}{Q_{1}(x)}-P_{1}(x)\frac{Q_{1}^{\prime }(x)}{Q_{1}(x)}\frac{Q(x)}{Q_{1}(x)}+P_{2}(x)\frac{Q(x)}{Q_{2}(x)} \\ &=&P_{1}^{\prime }(x)Q_{2}(x)-P_{1}(x)\left\{ \frac{Q_{1}^{\prime }(x)}{Q_{1}(x)}Q_{2}(x)\right\} +P_{2}(x)Q_{1}(x) \end{eqnarray*}

or

\begin{equation} P(x)=P_{1}^{\prime }(x)Q_{2}(x)-P_{1}(x)\left\{ T(x)-Q_{2}^{\prime }(x)\right\}+P_{2}(x)Q_{1}(x),\tag{2} \end{equation}

with $T(x)=Q^{\prime }(x)/Q_{1}(x)$, because from

\begin{equation*} Q^{\prime }(x)=\left\{ Q_{1}(x)Q_{2}(x)\right\} ^{\prime }=Q_{1}^{\prime }(x)Q_{2}(x)+Q_{1}(x)Q_{2}^{\prime }(x)=T(x)Q_{1}(x) \end{equation*}

we obtain

\begin{equation*} \frac{Q_{1}^{\prime }(x)}{Q_{1}(x)}Q_{2}(x)+Q_{2}^{\prime }(x)=T(x). \end{equation*}

To find the coefficients of the polynomials $P_{1}(x)$ and $P_{2}(x)$ equate the coefficients of like powers of $x$.

Application to

\begin{equation*} \frac{P(x)}{Q(x)}=\frac{5x^{3}+3x-1}{\left( x^{3}+3x+1\right) ^{3}}. \end{equation*}

Since

\begin{eqnarray*} Q(x) &=&\left( x^{3}+3x+1\right) ^{3} \\ Q^{\prime }(x) &=&9\left( x^{3}+3x+1\right) ^{2}\left( x^{2}+1\right) \\ Q_{1}(x) &=&\gcd \left\{ Q(x),Q^{\prime }(x)\right\} =\left( x^{3}+3x+1\right) ^{2} \end{eqnarray*}

and \begin{equation*} Q_{2}(x)=\frac{Q(x)}{Q_{1}(x)}=\frac{\left( x^{3}+3x+1\right) ^{3}}{\left( x^{3}+3x+1\right) ^{2}}=x^{3}+3x+1, \end{equation*}

we write

\begin{equation} \int \frac{5x^{3}+3x-1}{\left( x^{3}+3x+1\right) ^{3}}dx=\frac{P_{1}(x)}{ \left( x^{3}+3x+1\right) ^{2}}+\int \frac{P_{2}(x)}{x^{3}+3x+1}dx,\tag{3} \end{equation}

where

\begin{eqnarray*} P_{1}(x) &=&Ax^{5}+Bx^{4}+Cx^{3}+Dx^{2}+Ex+F \\ P_{2}(x) &=&Fx^{2}+Gx+H. \end{eqnarray*}

The identity $(2)$, with

\begin{equation*} T(x)=\frac{Q^{\prime }(x)}{Q_{1}(x)}=9\left( x^{2}+1\right), \end{equation*}

yields

\begin{eqnarray*} 5x^{3}+3x-1 &=&\left( 5Ax^{4}+4Bx^{3}+3Cx^{2}+2Dx+E\right) \left( x^{3}+3x+1\right) \\ &&-\left( Ax^{5}+Bx^{4}+Cx^{3}+Dx^{2}+Ex+F\right) \left\{ 9\left( x^{2}+1\right) -\left( 3x^{2}+3\right) \right\} \\ &&+\left( Gx^{2}+Hx+I\right) \left( x^{3}+3x+1\right) ^{2} \\ &=&Gx^{8}+\left( -A+H\right) x^{7}+\left( -2B+6G+I\right) x^{6} \\ &&+\left( 6H-3C+2G+9A\right) x^{5} \\ &&+\left( -4D+6B+9G+6I+2H+5A\right) x^{4} \\ &&+\left( 3C-5E+4B+6G+9H+2I\right) x^{3} \\ &&+\left( 3C-6F+G+6H+9I\right) x^{2} \\ &&+\left( 6I+H+2D-3E\right) x+\left( E+I-6F\right). \end{eqnarray*}

By equating coefficients we find

\begin{equation*} A=B=C=D=F=G=H=I=0,E=-1.\tag{4} \end{equation*}

Consequently,

\begin{eqnarray*} P_1(x) &=&-x \\ P_2(x) &=&0 \end{eqnarray*} and finally,

\begin{equation*} \int \frac{5x^{3}+3x-1}{\left( x^{3}+3x+1\right) ^{3}}dx=-\frac{x}{\left( x^{3}+3x+1\right) ^{2}}+C,\tag{5} \end{equation*}

as evaluated by you.

$\endgroup$
  • 2
    $\begingroup$ This is so nice method which I was unaware of +1. $\endgroup$ – Paramanand Singh Apr 4 '15 at 16:34
  • 2
    $\begingroup$ This is why I love this site. Something new to learn everyday. (And I who was about to put a comment to the question like: "Just do the substitution $u=-x/(x^3+3x+1)^2$", but I don't even think that'd be fun myself, after reading your nice and serious answer. $\endgroup$ – mickep Apr 4 '15 at 20:12
  • $\begingroup$ Answer to a similar question here. $\endgroup$ – Américo Tavares May 1 '15 at 22:53
10
$\begingroup$

$$ \begin{aligned}\int\frac{5x^3 + 3x - 1}{\left(x^3 + 3x + 1\right)^3}\,\mathrm{d}x &=\int\frac{5x^3 + 3x-1}{\left(\sqrt{x}\left(x^{5/2}+3\sqrt{x}+x^{-1/2}\right)\right)^3}\,\mathrm{d}x\\&=\int\frac{5x^3 + 3x-1}{x^{3/2}\left(x^{5/2}+3\sqrt{x}+x^{-1/2}\right)^3}\,\mathrm{d}x\\&=\int\frac{5x^{3/2}+3x^{-1/2}-x^{-3/2}}{\left(x^{5/2}+3\sqrt{x}+x^{-1/2}\right)^3}\,\mathrm{d}x\\&=\int\frac{2\,\mathrm{d}(x^{5/2}+3\sqrt{x}+x^{-1/2})}{\left(x^{5/2}+3\sqrt{x}+x^{-1/2}\right)^3}\\&=2\int\frac{\mathrm{d}\tau}{\tau^3}\\&=-\frac{1}{\tau^2}+C\\&=-\frac{1}{\left(x^{5/2}+3\sqrt{x}+x^{-1/2}\right)^2}+C\\&=\cdots\end{aligned} $$

$\endgroup$
8
$\begingroup$

Here is another solution... I also happen to think that it cannot be done with substitution.

$$\begin{aligned} \int \frac{5x^3+3x-1}{\left ( x^3+3x+1 \right )^3}\,dx &=\int \frac{-x^3-3x-1+6x^3+6x}{\left ( x^3+3x+1 \right )^3}\,dx \\ &= \int \frac{-x^3-3x-1+2x\left ( 3x^2+3 \right )}{\left ( x^3+x+1 \right )^3}\,dx\\ &= \int \frac{-\left ( x^3+3x+1 \right )^2+2x\left ( x^3+3x+1 \right )\left ( 3x^2+3x \right )}{\left ( x^3+3x+1 \right )^4}\,dx\\ &= \int \frac{-(x)'\left ( x^3+3x+1 \right )^2+x\left[ \left ( x^3+3x+1 \right )^2 \right]'}{\left ( x^3+3x+1 \right )^4}\,dx\\ &= \int \left [ -\frac{x}{\left ( x^3+3x+1 \right )^2} \right ]' \,dx = -\frac{x}{\left ( x^3+3x+1 \right )^2}+c, \; \; c \in \mathbb{R} \end{aligned}$$

$\endgroup$
  • $\begingroup$ +1 I would not discover your direct algebraic transformation of the integrand. Only if I worked backwards, from the solution to the original integral. $\endgroup$ – Américo Tavares May 6 '15 at 11:40
  • 1
    $\begingroup$ This is what I like doing when I work with integrals of this kind. I also liked your solution. I think I have seen the method before but I did not remember it. I guess it was just "luck" that I noticed it. If I do not , then I give up. :) $\endgroup$ – Tolaso May 6 '15 at 11:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.